Design and Development of Amphibious Hybrid Vehicle Body Structure - Hassan, Muhammad Zahir; Razali, Muhammad Razil; Halid, Mohd Shazni (2013)
Amphibious vehicle is a concept of vehicle that can be put forward for the purpose of commercialization, especially in the field of military and rescue operation. This paper present the development process involve in developing the composite bodywork of the Amphibious Hybrid Vehicle (AHV). It involves the process of design followed with the fabrication process. The total design method is used during the selection of the design stage and transformed into 2-dimensional and 3-dimensional form using CATIA V5 software. Upon completion of design, the fabrication process is implemented to complete the bodywork of the amphibious vehicle.